KEPASTIAN HUKUM AKIBAT MODAL YANG TIDAK DISETOR OLEH PEMEGANG SAHAM SETELAH PENDIRIAN PERSEROAN TERBATAS - Shanti Puruhita; Putra Hutomo; Taqiyuddin Kadir (Journal of Innovation Research and Knowledge, 2025)
Based on Article 1 number 1 of Law Number 40 of 2007 concerning Limited Liability Companies, we can see that shares are part of the Company's authorized capital where the founders of the company who deposit capital into the Company's cash when the PT was first established can also be referred to as shareholders. Provisions on the method of transferring rights to shares are generally submitted by the UUPT to the Articles of Association, unless otherwise specified by the UUPT. The transfer of rights to shares can be carried out by a deed of transfer of rights, either in the form of a deed made before a notary or a deed made privately so that it is clear that the UUPT only recognizes registered shares as in Article 48 of the UUPT which states that the company's shares are issued in the name of their owner, but in its implementation there are still many shareholders who do not attach proof of depositing capital into the company. The formulation of the problem in this study is what are the legal consequences of not depositing paid-in capital in a closed limited liability company and what is the legal certainty of shareholders of the company who do not deposit capital. The legal theory used in this study is the theory of legal consequences and the theory of legal certainty.The method used in this study is a normative legal research type, namely legal research conducted by examining library materials or secondary data only. The research approaches used are the Statutory Approach, Conceptual Approach, Analytical Approach, Case Approach and Data collection techniques are carried out by identifying and inventorying positive legal rules, examining library materials, and other sources of legal materials. For the Legal Material Analysis Technique using grammatical interpretation, historical interpretation, systematic interpretation, and legal construction methods.The results of this study indicate that shareholders who do not deposit capital into the company are considered to have violated Article 33 of the Limited Liability Company Law, so that their shareholder status can be revoked because they have not fulfilled their civil obligations so that they cannot be declared shareholders. As a result, these shareholders do not have the right to attend the GMS, vote, or receive dividends and remaining business results, and can be considered to have committed a breach of contract and an unlawful act, to avoid the risk in question, shareholders should carry out the obligation to deposit paid-in capital in the Company and this can be regulated more firmly in the Law so that a revision of the Limited Liability Company Law is needed.